Safety of a single low-dose of primaquine in addition to standard artemether-lumefantrine regimen for treatment of acute uncomplicated Plasmodium falciparum malaria in Tanzania. (December 2016) - Mwaiswelo, Richard; Ngasala, Billy; Jovel, Irina; Gosling, Roland; Premji, Zul; Poirot, Eugenie; Mmbando, Bruno; Björkman, Anders; Mårtensson, Andreas
Abstract Background This study assessed the safety of the new World Health Organization (WHO) recommendation of adding a single low-dose of primaquine (PQ) to standard artemisinin-based combination therapy (ACT), regardless of individual glucose-6-phosphate dehydrogenase (G6PD) status, for treatment of acute uncomplicatedPlasmodium falciparum malaria in Tanzania. Methods Men and non-pregnant, non-lactating women aged ≥1 year with uncomplicatedP. falciparum malaria were enrolled and randomized to either standard artemether-lumefantrine (AL) regimen alone or with a 0.25 mg/kg single-dose of PQ. PQ was administered concomitantly with the first AL dose. All drug doses were supervised. Safety was evaluated between days 0 and 28. G6PD status was assessed using rapid test (CareStart™) and molecular genotyping. The primary endpoint was mean percentage relative reduction in haemoglobin (Hb) concentration (g/dL) between days 0 and 7 by genotypic G6PD status and treatment arm. Results Overall, 220 patients, 110 per treatment arm, were enrolled, of whom 33/217 (15.2 %) were phenotypically G6PD deficient, whereas 15/110 (13.6 %) were genotypically hemizygous males, 5/110 (4.5 %) homozygous females and 22/110 (20 %) heterozygous females. Compared to genotypically G6PD wild-type/normal [6.8, 95 % confidence interval (CI) 4.67–8.96], only heterozygous patients in AL arm had significant reduction in day-7 mean relative Hb concentration (14.3, 95 % CI 7.02-21.55, p =0.045), however, none fulfilled the pre-defined haemolytic threshold value of ≥25 % Hb reduction. After adjustment for baseline parasitaemia, Hb, age and sex the mean relative Hb reduction was not statistically significant in both heterozygous and hemizygous/homozygous patients in both arms. A majority of the adverse events (AEs) were mild and unrelated to the study drugs. However, six (4.4 %) episodes, three per treatment arm, of acute haemolytic anaemia occurred between days 0 and 7. Three occurred in phenotypically G6PD deficient patients, two in AL and one in AL + PQ arm, but none in genotypically hemizygous/homozygous patients. All patients with acute haemolytic anaemia recovered without medical intervention. Conclusion The findings support that the WHO recommendation of adding a single low-dose of PQ to standard AL regimen is safe for the treatment of acute uncomplicatedP. falciparum malaria regardless of G6PD status in Tanzania. Trial registration number NCT02090036